Type-4 spinors: transmuting from Elko to single-helicity spinors - Villalobos, C. H. Coronado; Rogerio, R. J. Bueno [UNESP]; Sabbas, F. T. São (Springer Nature, 2019)
In this communication we briefly report an unexpected theoretical discovery which emerge from the mapping of Elko mass-dimension-one spinors into single helicity spinors. Such procedure unveils a class of spinor which is classified as type-4 spinor field within Lounesto classification. In this paper we explore the underlying physical and mathematical contents of the type-4 spinor.